Peran PBB Dalam Penyelesaian Konflik Rusia Dengan Ukraina - Putri Permata A Harahap; Siti Zahra Siagian; Seevaira Chyta Simanullang; Victoria Grace Daily; Yuli Indriani Lubis; Yeni Yolanda Simbolon (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research examines the impact of the Russian-Ukrainian conflict on efforts to resolve the humanitarian crisis. His focus includes Russia's use of the veto in the UN Security Council, the humanitarian impact, and the role of the UN. Russia's 2014 annexation of Crimea was the start of the conflict, with Russia's veto hampering the UN response. Conflicts that result in humanitarian crises, massive displacement, human rights violations and loss of life. This research also explores the UN's role in mediation, dealing with political obstacles and tensions on the ground. Through analysis of previous literature and research, this research seeks a deeper understanding of the dynamics of this conflict and the role of international institutions in overcoming the crisis. Its findings illustrate that Russia's veto hinders decisive action by the UN, while the humanitarian crisis and political tensions complicate the UN's mediation role. This research contributes to understanding the impact of international conflict and the challenges international institutions face in maintaining peace and dealing with humanitarian crises.